Does subsidized care for Toddlers increase maternal labor supply? Evidence from a large-scale expansion of early childcare - Kai-Uwe Müller; Katharina Wrohlich (Deutsches Institut für Wirtschaftsforschung (DIW), 2018)
Expanding public or publicly subsidized childcare has been a top social policy priority in many industrialized countries. It is supposed to increase fertility, promote children's development and enhance mothers' labor market attachment. In this paper, we analyze the causal effect of one of the largest expansions of subsidized childcare for children up to three years among industrialized countries on the employment of mothers in Germany. Identification is based on spatial and temporal variation in the expansion of publicly subsidized childcare triggered by two comprehensive childcare policy reforms. The empirical analysis is based on the German Microcensus that is matched to county level data on childcare availability. Based on our preferred specification which includes time and county fixed effects we find that an increase in childcare slots by one percentage point increases mothers' labor market participation rate by 0.2 percentage points. The overall increase in employment is explained by the rise in part-time employment with relatively long hours (20-35 hours per week). We do not find a change in full-time employment or lower part-time employment that is causally related to the childcare expansion. The effect is almost entirely driven by mothers with medium-level qualifications. Mothers with low education levels do not profit from this reform calling for a stronger policy focus on particularly disadvantaged groups in coming years.
Keywords: J22; J13; H43; 330; childcare provision; mother's labor supply; generalized difference-in-difference